Protein O‐GlcNAcylation impairment caused by N‐acetylglucosamine phosphate mutase deficiency leads to growth variations in Arabidopsis thaliana. (9th March 2023) - Jia, Xiaochen; Zhang, Hongyan; Qin, Hongqiang; Li, Kuikui; Liu, Xiaoyan; Wang, Wenxia; Ye, Mingliang; Yin, Heng
SUMMARY: As an essential enzyme in the uridine diphosphate (UDP)‐GlcNAc biosynthesis pathway, the significant role of N ‐acetylglucosamine phosphate mutase (AGM) remains unknown in plants. In the present study, a functional plant AGM ( At AGM) was identified from Arabidopsis thaliana . AtAGM catalyzes the isomerization of GlcNAc‐1‐P and GlcNAc‐6‐P, and has broad catalytic activity on different phosphohexoses. UDP‐GlcNAc contents were significantly decreased in At AGM T‐DNA insertional mutants, which caused temperature‐dependent growth defects in seedlings and vigorous growth in adult plants. Further analysis revealed that protein O ‐GlcNAcylation but not N ‐glycosylation was dramatically impaired in Atagm mutants due to UDP‐GlcNAc shortage. Combined with the results from O ‐GlcNAcylation or N ‐glycosylation deficient mutants, and O ‐GlcNAcase inhibitor all suggested that protein O ‐GlcNAcylation impairment mainly leads to the phenotypic variations of Atagm plants. In conclusion, based on the essential role in UDP‐GlcNAc biosynthesis, AtAGM is important for plant growth mainly via protein O ‐GlcNAcylation‐level regulation. Significance Statement: In plants, research of the uridine diphosphate (UDP)‐GlcNAc biosynthesis pathway and insights into UDP‐GlcNAc function and mechanism in terms of protein glycosylation regulation are still insufficient till now. Our study identified a functional AGM, the third enzyme in the Arabidopsis thaliana UDP‐GlcNAc biosynthesis pathway, and found that AtAGM is important for plant growth mainly via protein O ‐GlcNAcylation‐level modulation.